My blade, your back - Moronova, K. M. (Moronova, K. M. Dark forces., 2025)
"Broken. Lost. Unforgiven. One month after surviving the Under Trials, Emery Maves finds herself in a world she doesn't recognize-with a man whose cold eyes are haunted by secrets she can't remember. Stripped of her memories, Emery is tormented by dreams of danger, death, and deceit. The only constant is the lure of the experimental drug that shatters her mind but leaves her almost invincible-and the dangerous pull of the man called Mori. Cameron Mortem is fighting a battle he thought he'd already lost. He knows letting Emery in could destroy them both, but her amnesia is a curse neither of them can outrun. Forced together on a high-stakes level black mission that goes disastrously wrong, they find themselves thrust deeply into the underworld of the black market with an unexpected foe. But as old scars are torn open and hidden plots unravel, Emery discovers she's more tangled in this world than she ever imagined. And Cameron will have to face the one person he fears most: himself. Loyalties will be tested. Secrets will be weaponized. Their bond-once forged in blood-may be the only thing that can save them. If they don't lose themselves first"-- Provided by publisher.